THU0646 Evaluating the quality of care for rheumatoid arthritis. (12th June 2018) - Barber, C.; Marshall, D.; Szefer, E.; Thompson, D.; Lacaille, D.
Abstract : Background: The Arthritis Alliance of Canada (AAC) has developed performance measures (PMs) to evaluate RA care quality. Objectives: To operationalize and report on 4 PMs using administrative data for British Columbia (BC), Canada: PM1) percentage of patients with new onset RA with at least one visit to a rheumatologist in the first year after diagnosis, PM2) percentage of RA patients under the care of a rheumatologist seen in follow-up at least once per year, PM3) percentage of RA patients dispensed a disease modifying anti-rheumatic drug (DMARD) during the measurement year, PM4) time to DMARD therapy in new onset RA. Methods: All patients with RA visits between 01/01/1997 and 31/12/2009 in BC were identified using health administrative data and followed until December 2014. Cases were identified by ≥2 physician billing codes for RA ≥8 weeks but ≤5 years apart. For this study, only cases age >18 who were seen by a rheumatologist at some point over follow-up were included. PM1: The percentage of incident RA cases with at least one visit to a rheumatologist within one year of their first RA visit was evaluated. PM2: The proportion of prevalent RA cases having at least one visit per year was calculated for those under rheumatology care. PM3: The percentage of prevalent RA patients dispensed a DMARD (including biologic agents and small molecule inhibitors) was calculated. PM4: time from RA onset (defined as first RA visit) to DMARD therapy was reported (in the calendar year of RA incidence), using median and 90th percentile wait time, as well as the proportion meeting the benchmark of 14 days. Results: The cohort included 18 976 incident and 29 639 prevalent RA cases. The percentage of patients seen by a rheumatologist within 1 year from RA diagnosis increased over time, while the percentage of RA patients under the care of a rheumatologist seen in yearly follow-up declined steadily overtime. Further analysis (data not shown) suggests this is due to having more people with longer follow-up in the latter years, and lost to follow-up increasing over time, rather than a true calendar year effect. The percentage of RA patients dispensed a DMARD was suboptimal (56%>65%). Of note, patients were not necessarily seen by a rheumatologist during the measurement year. The median time to DMARD improved over time to 23 days in 2009, with roughly one third receiving a DMARD within the benchmark of 14 days. Conclusions: The present study represents the first time the AAC's PMs have been tested in administrative data and highlights where the measures are being met and potential gaps in care which require further examination. Disclosure of Interest: None declared